2008
DOI: 10.1152/ajplung.00250.2007
|View full text |Cite
|
Sign up to set email alerts
|

TRX-ASK1-JNK signaling regulation of cell density-dependent cytotoxicity in cigarette smoke-exposed human bronchial epithelial cells

Abstract: Lee YC, Chuang C-Y, Lee P-K, Lee J-S, Harper RW, Buckpitt AB, Wu R, Oslund K. TRX-ASK1-JNK signaling regulation of cell density-dependent cytotoxicity in cigarette smokeexposed human bronchial epithelial cells. Am J Physiol Lung Cell Mol Physiol 294: L921-L931, 2008. First published February 15, 2008 doi:10.1152/ajplung.00250.2007.-Cigarette smoke is a major environmental air pollutant that injures airway epithelium and incites subsequent diseases including chronic obstructive pulmonary disease. The lesion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Because cigarette smoke is a complex combination of many compounds that could affect epithelial-cell functions in different ways, we believed it most valid to study complete mixtures initially, for a better understanding of the overall effects of cigarette smoke on airway defense. Some reports demonstrate significant cytotoxicity of cigarette smoke, particularly with subconfluent cells, and thus we chose well-defined conditions and smoke concentrations, and also monitored to avoid cytotoxicity (28)(29)(30). In addition, in some experiments, epithelial cells were exposed to CSE for 48 hours before treatment, to verify the effects and assess cytotoxicity, because humans are often passively or actively exposed to cigarette smoke for longer durations.…”
Section: Discussionmentioning
confidence: 99%
“…Because cigarette smoke is a complex combination of many compounds that could affect epithelial-cell functions in different ways, we believed it most valid to study complete mixtures initially, for a better understanding of the overall effects of cigarette smoke on airway defense. Some reports demonstrate significant cytotoxicity of cigarette smoke, particularly with subconfluent cells, and thus we chose well-defined conditions and smoke concentrations, and also monitored to avoid cytotoxicity (28)(29)(30). In addition, in some experiments, epithelial cells were exposed to CSE for 48 hours before treatment, to verify the effects and assess cytotoxicity, because humans are often passively or actively exposed to cigarette smoke for longer durations.…”
Section: Discussionmentioning
confidence: 99%
“…JNK activation may also play a role in COPD. Cigarette smoke cytotoxicity in airway epithelial cells is mediated via activation of JNK (Lee et al, 2008).…”
Section: Jun Nh2-terminal Kinase Inhibitorsmentioning
confidence: 99%
“…Thioredoxin is normally bound to ASK1 to suppress its activity, and ASK becomes activated when thioredoxin is reduced by oxidative stress. ASK1 mediates the cytotoxicity of cigarette smoke in airway epithelial cells, which is inhibited by the closely associated antioxidant thioredoxin (Lee et al, 2008). ASK1 is a good potential target for COPD, and several small molecule inhibitors have been identified (Starosyla et al, 2015).…”
Section: E Apoptosis Signal-regulating Kinase-1 Inhibitionmentioning
confidence: 99%
“…10), suggesting that MIR517A could be associated with the pathway. A recent study [33] demonstrated that overexpression of TXN attenuated cigarette smoke extract-mediated cell death and MAPK8/ 9/10 activation in human bronchial epithelial cells. Thus, a possible function of MIR517A could be to regulate signal transduction mediated by TNF and/or other death ligands, although more detailed studies are necessary.…”
Section: Proteome Analysis Of Mir517a-regulated Proteins In Bewo Cellsmentioning
confidence: 99%